Nativos digitales: el reto de enseñar Derecho en la actualidad - Mesa Rada, Diego Javier (2014)
This work aims to be a creative center of consciousness while a stimulant for law teachers who are perhaps as sometimes happened to the author of these lines, at a crossroads on how they should deal with the challenge of teaching law for the digital natives. This paper is not a preparatory guide, it is a reflective work from their own experience, whose quest is to unsettle teachers in law schools so that everyone, from your area and your perspective, imagine the best strategy to meet the challenge of forming digital natives, transforming them into integral lawyers who possess the knowledge and skills necessary to properly navigate the legal world of today and tomorrow.